Mass conservation issues of moving interface flows modelled by the interface capturing approach - Kaceniauskas, A (Mechanika (Kaunas, Lithuania : 1995), 2008)
The paper describes the development of the mass correction technique for viscous incompressible flows in-cluding moving interfaces. The dam break problem is solved by the pseudo-concentration method based on the interface capturing approach. The detailed numerical in-vestigation of the nonlinear solution of the mass conserva-tion equation is presented. The interface sharpening gov-erned by different strategies is examined. The developed mass correction technique is validated on two finite ele-ment meshes of different resolution.